Mitigating inter-carrier interference in orthogonal frequency division multiplexing system using scaled alpha pulse shaping technique - Ibrahim, Nor Adibah (2015)
Orthogonal Frequency Division Multiplexing (OFDM) is a promising technique for broadband wireless communication system, especially in fourthgeneration (4G) applications. However, a special problem in OFDM is its vulnerability to frequency offset errors due to which the orthogonality is destroyed that results in Inter-Carrier Interference (ICI). ICI causes power leakage among subcarriers, thus degrading overall system performance. ICI is severe and often difficult to remove because the properties of additive noise vary for different carriers. Pulse shaping is among the techniques used to reduce ICI effect. In this thesis, a new pulse shape namely, Scale Alpha for ICI mitigation in OFDM system is proposed. The pulse is modelled and simulated using Matlab software. The pulse performance in reducing ICI is compared to the Franks pulse which is also known as the best pulse among Nyquist pulses. Impulse response, eye diagram, and ICI power reduction performances have also been carried out. The result shows 76.93 dB of ICI reduction compared to the Franks pulse when alpha is equal to 1. This advantage of new Scale Alpha pulse can be applied in the applications of wireless model system especially in 4G applications.